Utang Luar Negeri dan Problem Kemiskinan Negara Berkembang (Tinjauan Teoritis) - Sitepu, Dewi Sinorita (Global: Jurnal Politik Internasional, 2005)
This article tries to analyze the correlation between foreign debt and poverty problem in developing countries. It is started on an assumption that foreign debt was initially aimed to solve poverty problem, which limits the capability of those countries to involve into global economic system. In fact, foreign debt which is designed to help developing countries overcoming poverty problem, only makes this problem worse. A global economic development policy through massive foreign aid solution has entrapped developing countries on continuous debt, and after several years of foreign aid, developing countries remain poor and unequal. Thus, Michael Hendri Bouchet argued that moving along the graduated scale from threat of default to normalization of debtor-creditor relationship requires the maintenance of an atmosphere of mutual interest and not merely of forced solidarity. A better understanding of each group of actors' stakes and objectives is a crucial condition for implementing such an enhanced debt strategy.